Predictors of academic achievements in online peer learning among undergraduate students in a Malaysian Public University - Amin, Ibrahim Mohammed Hamad (2016)
An online peer learning through social media tools such as Facebook, Twitter, YouTube and Instagram has been networking interrelated undergraduates as social groups in higher learning institutions. In that respect, it has become an emerging phenomenon in the academia. Yet, not much is known about the effect of social media on the undergraduates‟ academic achievement. Therefore, the main purpose of this study is to identify factors influencing academic achievement in online peer learning among undergraduate students of one of the Malaysian public and Research Universities. Specifically, the study is focused on investigating: i) students‟ peer engagement, academic self-efficacy, performance expectancy, social influence, peer feedback and collaboration, ii) relationship of students‟ peer engagement, academic self-efficacy, social influence, peer feedback and collaboration with students‟ academic achievement while practising online peer learning via social media and iii) to predict factors that influencing students‟ academic achievement among undergraduate students in Universiti Putra Malaysia (UPM). The study was based on the quantitative method in nature with a correlational design using a set of the questionnaire as instrument adapted from previous studies and validated by a panel of experts. A pilot study was conducted on 30 undergraduate students at UPM to check the reliability of the measurements. The value of Cronbach‟s Alpha is greater than 0.70. The target population of this study is undergraduate students of the UPM. The sampling technique is stratified. A total of 376responseswere collected. The data was analyzed using Statistical Package for the Social Sciences (SPSS) version 22.0. The finding of regression analysis indicated that five of the variables have a significant effect while the only peer feedback has an insignificant effect. The most important factor is social influence (β = .210, p p <. 05), and academic self-efficacy (β =.120, p <.05). The model explained 38.9% of the variation in the academic achievement of undergraduate students at UPM. This study is useful for the decision makers at the university. More effort has to be made to encourage the students to involve effectively on the peer learning via social media. As lecturers and point, rewards can enhance students‟ collaboration which will lead to better academic achievement. The study confirms that UTAUT is able to explain the variation in the usage of online peer learning via social media to improve academic achievement. It also confirms the validity of the Sociocultural Theory. The collaboration can take place in an online environment and lead to similar results of peer teaching and collaborate with each other. As a result, this study confirms that collaboration between peer in an online environment is valid and able to predict the academic achievement. Social Cognitive Theory was validated by the findings of this study.